The Legal Analysis of Copyright Protection for E-Books in the Form of Non-Fungible Token (NFTs) - Christina, Christina; Amboro, Florianus Yudhi Priyo; Hutauruk, Rufinus Hotmaulana (Universitas Internasional Batam, 2023)
Non-Fungible Tokens (NFTs) serve as a digital platform that aids creators of digital works, particularly E-Books, in marketing or introducing their creative outputs. This platform offers easy access and high-security systems to safeguard the copyright of E-Book creators. This study aims to analyze and provide insights into the copyright protection of E-Book works in the form of NFTs, under the perspective of Copyright Law. Additionally, the study seeks to determine whether NFT transactions can serve as a solution for Intellectual Property protection in Indonesia. The research employs a normative legal research method, utilizing literature review and descriptive techniques. The findings reveal that NFTs can indeed offer a solution for intellectual property protection in Indonesia. By transforming works into NFTs, their copyright is protected through ownership tokens that are automatically integrated into the blockchain (digital ledger).